2019
DOI: 10.1177/0391398819833372
|View full text |Cite
|
Sign up to set email alerts
|

Flow rate estimation of a centrifugal blood pump using the passively stabilized eccentric position of a magnetically levitated impeller

Abstract: Flow rate estimation for ventricular assist devices without additional flow sensors can improve the quality of life of patients. In this article, a novel flow estimation method using the passively stabilized displacement of a magnetically levitated impeller is developed to achieve sufficient accuracy and precision of flow estimation for ventricular assist devices in a simple manner. The magnetically levitated impeller used is axially suspended by a magnetic bearing in a centrifugal blood pump that has been dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 26 publications
(48 reference statements)
3
21
1
Order By: Relevance
“…Details of the PSDM were reported in our previous study. 11 In the previous report, it was shown that the radial component of the gravity force vector (F Gr ) was not exerted on the impeller due to horizontal operation of the device. This was because the gravity direction was the same as the actively controlled direction of the axial axis; therefore, the correlation between Q and (x, y), which is the basis of the PSDM, was not affected by gravity.…”
Section: Psdm Backgroundmentioning
confidence: 98%
See 1 more Smart Citation
“…Details of the PSDM were reported in our previous study. 11 In the previous report, it was shown that the radial component of the gravity force vector (F Gr ) was not exerted on the impeller due to horizontal operation of the device. This was because the gravity direction was the same as the actively controlled direction of the axial axis; therefore, the correlation between Q and (x, y), which is the basis of the PSDM, was not affected by gravity.…”
Section: Psdm Backgroundmentioning
confidence: 98%
“…Recently, our group developed a novel flow rate estimation method using passively stabilized radial displacement of a magnetically levitated (maglev) impeller in a centrifugal blood pump with an axial magnetic suspension system (hereinafter referred to as the passively stabilized displacement method (PSDM)). 11 The PSDM is a simple system that does not require blood viscosity measurements, but showed high performance. The blood viscosity measurements compromised the simplicity of the flow rate estimation with the conventional flow rate estimation method using the motor current.…”
Section: Introductionmentioning
confidence: 99%
“…Various groups have already shown the feasibility of Q and ∆p estimation for heart assist devices from other signals such as ω and motor power-P [10,11], ω, and motor torque-τ [12,13], ω and I [14][15][16][17][18], or even impeller radial displacement [19]. Almost all also considered the effects of blood viscosity µ [10][11][12][14][15][16][17][18][19][20]. Most of the efforts are focused on steady state estimation or averaging over many samples [10,11,19].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all also considered the effects of blood viscosity µ [10][11][12][14][15][16][17][18][19][20]. Most of the efforts are focused on steady state estimation or averaging over many samples [10,11,19]. However, some efforts have been put into dynamic estimations with high bandwidth [15,16], e.g., Moscato et al reported an root mean squared error (RMSE) of 252 mL .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we developed a novel flow rate estimation method using passively stabilized radial displacement of a magnetically levitated (maglev) impeller in a centrifugal blood pump with an axial magnetic suspension system (hereinafter, referred to as the passively stabilized displacement method (PSDM)). 11,12 The PSDM is a simple system that does not require blood viscosity measurements but yields high performance. Therefore, reliable and real-time flow rate estimation can be achieved with PSDM.…”
Section: Introductionmentioning
confidence: 99%